A new universal simplified adhesive: 36-Month randomized double-blind clinical trial. Issue 9 (September 2015) - Loguercio, Alessandro D.; de Paula, Eloisa Andrade; Hass, Viviane; Luque-Martinez, Issis; Reis, Alessandra; Perdigão, Jorge
Abstract Statement of the problem It is still debatable which technique should be used with universal adhesives, either etch-and-rinse (wet or dry) or self-etch strategy (with or without selective enamel etching). Purpose of the study To evaluate the 36-month clinical performance of Scotchbond Universal Adhesive (SU, 3M ESPE) in non-carious cervical lesions (NCCLs) using two evaluation criteria. Methods/materials Thirty-nine patients participated in this study. Two-hundred restorations were assigned to four groups: ERm: etch-and-rinse + moist dentin; ERd: etch-and-rinse + dry dentin; Set: selective enamel etching; and SE: self-etch. The same composite resin was inserted for all restorations in up to 3 increments. The restorations were evaluated at baseline and at 6-, 18-, and 36-months using both the FDI and the USPHS criteria. Statistical analyses were performed with Friedman repeated measures ANOVA by rank and McNemar test for significance in each pair (α = 0.05). Results Eight restorations (ERm: 1; ERd: 1; Set: 1 and SE: 5) were lost after 36 months, but only significant for SE when compared with baseline (p = 0.02 for either criteria). Marginal staining occurred in 6.8% of the restorations (groups ERm, ERd, and Set) and 17.5% of the restorations (group SE), with significant difference for each group when compared with baseline using the FDI criteria (p < 0.04), while statistical significance was reached only for SE when compared with baseline using the USPHS criteria (p < 0.03). Twenty-eight and 49 restorations were scored as bravo for marginal adaptation using the USPHS and FDI criteria, respectively, with significant difference for each group when compared with baseline (p < 0.05). Conclusions While there was no statistical difference among bonding strategies when a universal adhesive was used, there were signs of degradation when the universal adhesive was applied in SE mode. The FDI criteria remain more sensitive than the USPHS criteria, especially for the criteria marginal staining and marginal adaptation.